2004
DOI: 10.1128/iai.72.8.4654-4661.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Two-Component Regulator CpxAR in the Virulence of Salmonella enterica Serotype Typhimurium

Abstract: The CpxAR (Cpx) two-component regulator controls the expression of genes in response to a variety of environmental cues. The Cpx regulator has been implicated in the virulence of several gram-negative pathogens, although a role for Cpx in vivo has not been demonstrated directly. Here we investigate whether positive or negative control of gene expression by Cpx is important for the pathogenesis of Salmonella enterica serotype Typhimurium. The Cpx signal pathway in serotype Typhimurium was disrupted by insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
112
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 45 publications
3
112
1
Order By: Relevance
“…The CpxR response regulator has been shown to be involved in the pathogenesis of Salmonella enterica, Shigella sonnei, enteropathogenic E. coli, and Yersinia sp., and in most cases its involvement was related to contact with eukaryotic cells (7,8,25,40,41). The PmrA response regulator has been shown to be involved in the virulence of S. enterica, Pseudomonas aeruginosa, and Francisella sp., and its involvement was mainly related to its relationship with the PhoP response regulator and resistance to antimicrobial peptides (13,33,35,55).…”
Section: Discussionmentioning
confidence: 99%
“…The CpxR response regulator has been shown to be involved in the pathogenesis of Salmonella enterica, Shigella sonnei, enteropathogenic E. coli, and Yersinia sp., and in most cases its involvement was related to contact with eukaryotic cells (7,8,25,40,41). The PmrA response regulator has been shown to be involved in the virulence of S. enterica, Pseudomonas aeruginosa, and Francisella sp., and its involvement was mainly related to its relationship with the PhoP response regulator and resistance to antimicrobial peptides (13,33,35,55).…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with and shed light on previous studies of the Cpx response in other pathogens. For example, the interruption of cpxR in Salmonella enterica serovar Typhimurium and Yersinia enterocolitica had no observable effect on virulence in an animal model (27,28). Alternatively, CpxRϳP has been shown to negatively regulate P pilus expression in uropathogenic E. coli (26).…”
Section: Discussionmentioning
confidence: 99%
“…Elegant work with uropathogenic E. coli demonstrated that CpxRϳP binds to a region controlling pap phase variation and inhibits P pilus expression in vivo (26,29). In Salmonella enterica serovar Typhimurium, a cpxA mutant decreases expression of a major regulator of invasion genes, HilA (46), and exhibits a diminished ability to attach to and invade eukaryotic cells (28). Lastly, a CpxR homologue positively regulates transcription of the icm-dot type IV secretion system in Legionella pneumophila (23).…”
mentioning
confidence: 99%
“…Each response triggers a signaling cascade that leads to the regulation of factors needed to combat envelope damage or to respond to the stress (5). Some envelope stress response signaling has been linked to virulence in Gram-negative bacteria (7,8). For instance, the RcsBC signaling system enhances the locus of enterocyte effacement (LEE) and the adherence phenotype of the STEC O157:H7 isolate TW14359, the isolate responsible for a 2006 outbreak in the United States (8).…”
mentioning
confidence: 99%
“…For instance, the RcsBC signaling system enhances the locus of enterocyte effacement (LEE) and the adherence phenotype of the STEC O157:H7 isolate TW14359, the isolate responsible for a 2006 outbreak in the United States (8). CpxAR is involved in bacterial adhesion (6,7) and is activated during prophage induction in E. coli (9). Finally, BaeSR, which mediates increased resistance to toxic compounds (10), is related to envelope biogenesis (10) and could regulate the expression of surface elements (10).…”
mentioning
confidence: 99%